The knowledge of nursing technical course students about violence against women (Research, Society and Development, 2021)
Objective: to describe the knowledge of students of a certificate program in nursing concerning violence against women. Method: Descriptive, exploratory and transverse study with a quantitative approach including the participation of 84 students, who answered a validated questionnaire, in 2017. Descriptive analysis was used. Results: The students demonstrated knowledge about the definition of the most common types of violence, the main aggressors and the aggravating factors resulting from violence against women; they recognized that nursing has the attribution to approach that kind of violence, the necessity of elaborating safety plans and conducting women exposed to violence to social institutions. Nevertheless, they have poor knowledge of the violence incidence, the frequency with which women seek help, the assistance protocols regarding sexually abused women and the compulsory character of notifying the cases. Conclusion: The study showed gaps in the educational background of licensed practical nurses and the need of including theory and practice in the program related to violence against women.